On the Optimal Size of Public Sector under Rent-Seeking competition from State Coffers - Hyun Park; Apostolis Philippopoulos; Vangelis Vassilatos (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper incorporates competition for fiscal transfers (or, equivalently, rent seeking from state coffers) into a standard general equilibrium model of economic growth and endogenously chosen fiscal policy. The government generates tax revenues, but then each selfinterested individual agent tries to extract, for his own personal benefit, a fraction of these revenues. Extracted tax revenues could alternatively be used to finance economy-wide infrastructure. We look at a Nash equilibrium in individual agents' behavior, and then investigate what the society should do to discourage rent-seeking competition. The focus is on the optimal size of public sector.
Keywords: 330; social conflict; fiscal policy; economic growth